HUBUNGAN SKOR SERTIFIKASI TOEIC DENGAN KESEMPATAN BERGABUNG DI PERUSAHAAN MULTINASIONAL: STUDI LULUSAN POLITEKNIK ENJINERING INDORAMA - Rahayu, Widya Andayani; Mulyani, Heti; Herman, Sukrina; Faizzati, Fauziah; Hindrasari, Hestisara (LPPM Politeknik Enjinering Indorama, 2025)
The purpose of the study is to determine the correlation between the TOEC certification scores of Politeknik Enjinering Indorama graduates and their opportunities to join multinational companies. Twenty-eight graduates of Manufacturing Engineering/Mechanical Engineering, Mechatronics Engineering/Mechatronics, Software Engineering, and Electrical Engineering study programs who graduated from 2022 to 2024 were the respondents in this study. A qualitative approach was used in this study with simple data analysis based on TOEIC certification scores and questionnaires obtained from respondents representing the entire population. The result showed that the respondents’ English communication skills were in the lower-middle category with fairly high variability, with the respondents’ TOEIC certification scores showing an average value of 42,66 and a standard deviation of 15,75. The average score for opportunities to join multinational companies was quite high at 78,10 with a standard deviation of 12,38. This data analysis indicates that the majority of respondents have relatively good opportunities to join multinational companies. The correlation coefficient R2 of 0,0128 and the regression model y = 0,089x + 74,298 indicate that every 1-point increase in TOEIC score only increases the opportunity to join by 0,089% which directly shows a very minimal correlation. Thus, it can be concluded that the TOEC scores are not a reliable predictor to indicate the opportunities to join the multinational companies.